The importance of local environmental, hydrogeomorphological and spatial variables for beta diversity of macrophyte assemblages in a Neotropical floodplain. (8th February 2019) - Schneider, Berenice; Cunha, Eduardo R.; Espínola, Luis A.; Marchese, Mercedes; Thomaz, Sidinei M.
Abstract: Questions: Understanding the processes that determine the variation in community composition (β‐diversity) is a major challenge in ecology, evolution, and conservation. Here we assess the importance of abiotic variables associated with local environmental features, hydrogeomorphology, and space to explain β‐diversity patterns in macrophytes by addressing the following questions: (1) Which are the sets of environmental, hydrogeomorphological, and spatial variables that contribute significantly to the spatial variation of macrophytes? (2) Which are their relative contributions to explaining the total β‐diversity, nestedness and turnover of macrophyte assemblages? Study Site: Middle Paraná River floodplain, Argentina. Methods: We sampled 20 lakes at low and high water levels in the Middle Paraná River floodplain. To investigate the relationship of total β‐diversity, turnover and nestedness with explanatory variables, we used the constrained analysis of principal coordinates (CAP). We used variation partitioning to assess the proportion of the variation related to each subset of variables (environmental, hydrogeomorphological and spatial). Results: Among four alternatives considered to explain the spatial structure, the distance between lakes by watercourses best described the spatial organization of β‐diversity. Species turnover was largely explained by hydrogeomorphological variables, followed by spatial descriptors, whereas nestedness was exclusively related to spatial variables. Conclusions: In the Middle Paraná River floodplain β‐diversity of macrophyte communities is partly shaped by turnover (mainly driven by the hydrogeomorphology of the floodplain) and nestedness (resulting from dispersal limitation by watercourses), but it also seems to be randomly organized (possibly because of random colonization and extinction, due to disturbances such as floods). Our work indicates that environmental pressures reflect differences between macrophyte communities of lakes with different geomorphological and hydrographical conditions. This suggests that certain ecological processes (such as species sorting) are driven at a higher degree by hydrogeomorphology than by local environment. Abstract : We show that β‐diversity of aquatic macrophytes is shaped by hydrogeomorphology (H), local environmental variables (E), and spatial structure (S) within a river–floodplain system. Hydrogeomorphology was the major driver of turnover suggesting species sorting due to niche processes. Space mostly contributed to species nestedness, suggesting that species loss is mostly related to dispersal limitation in the landscape.